Effect of Sheet Thickness during Superplastic Forming of AZ31B Alloy into a Hemispherical Die - Balaguru, S.; Siva Kumar, K.; Deenadayalan, G.; Sathishkumar, P. (International Journal of Engineering and Technology, 2026)
This paper deals with the effect of various combinations of temperature and pressure in the Superplastic forming process of AZ31B Magnesium alloy of different thickness into a hemispherical die. Using the time taken and the corresponding depth formed, the values of strain, strain rate and strain rate sensitivity were calculated. From these values, graphs were plotted. From the graphs, the effective pressure and temperature combination for specific thickness was determined.
Keywords: Superplastic forming; Magnesium alloy; Hemispherical die.